ANALISIS LAPORAN KEUANGAN DENGAN METODE Z SCORE UNTUK MEMPREDIKSI KEBANGKRUTAN BANK (STUDI KASUS BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Pramono, Joko (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2009)
Abstract This research intends for knowing (kinerja) the bank finance that registrated in Indonesian stock exchange 2005 – 2007. By used the Z Score analysis Altman, so it will has a potential for bankrupt or not.Data which used in this research is the secondary data like Bank finance report, which get from BEI website and BI website and Indonesian Capital Market Directory Report 2008, 2007, 2006. Next, that data was analyzed by used the discrimination analysis (Z score) Altman, version four variable, there are : Z = 6,56 (X1 ) + 3,26 ( X2 ) + 6,72 ( X3 ) + 1,05 ( X4 ). Z value can be categoried in three story, there are bankrupt if the value is £1,10, Grey area if the value is between 1,10 – 1,70 (it means bank still has a opportunity to become good, if the manajemen repaired mechanishm it enterprise) and good, if the value is >2,60The research produced that in 2005 from 25 bank go public known 19 bank have a potention bankrupt and 6 bank enter in grey area category.And then in 2006 from 27 bank go public, there are 16 bank have a potention for bankrupt, 11 bank in grey area category and there only one bank which has a good category, this is Bank UOB BuanaSome bank that have a bankrupt potential turned out until this time still exist, it happened because bank mechanism evaluation did by Bank Indonesia by used the finance ratio CAMEL (Capital Asset Management Earnings Liquidity) Key Words : Financial Reports, Z Score Analysis, financial ratios